Africanisation of international investment law for sustainable development: challenges. Issue 1 (10th March 2021) - Laryea, Emmanuel T.; Fabusuyi, Oladapo O.
Abstract : Purpose: The purpose of this study is to critically examine the move to Africanise international investment law (IIL) aimed at promoting sustainable development on the continent. Design/methodology/approach: The study analyses the move by African countries to "Africanise" IIL by incorporating specific and innovative provisions and features in their international investment agreements (IIAs) for the benefit of African economies. This is evidenced by provisions in African regional investment instruments such as the 2007 Common Market of Eastern and Southern Africa Investment Agreement and the 2008 Economic Community of West African States Supplementary Act on Investments produced by the different African regional economic communities (RECs), new-generation IIAs such as the 2016 Nigeria-Morocco IIA and the China-Tanzania IIA and the African Union's Pan-African Investment Code 2016. The common features of these instruments include linking the objective of investment promotion and protection to sustainable development; excluding portfolio investments; including provisions on investor-obligations; and reserving wide scope of regulatory space for host-states, including the ability to take emergency measures without incurring liability to investors. Some of these provisions are rare in IIAs. Findings: The study finds that, while the efforts are commendable, there are real challenges. Firstly, there are inconsistencies in the regimes existing on the continent due to differences in the contents of the international investment instruments promulgated by the different RECs, and also differences in the content of IIAs signed by some member-states of the RECs with countries external to the RECs. Secondly, there are governance gaps and a lack of enforcement in practice, which would undermine the effectiveness of the laws being forged. Thirdly, the Africanised IIL alone would not attract investment if other important determinants, such as critical infrastructure, remain lacking. Fourthly, there is under-representation of Africa in the arbitral institutions that develop and enrich the laws, which, if it continues, would undermine the effectiveness of the Africanisation provisions being included in IIAs. Research limitations/implications: While the research discusses both law and policy, more is discussed of the law, owing to space limitation. Practical implications: It is anticipated that this research will impact the content of the investment protocol under the African continental free trade area and beyond and will prompt review of existing and future IIAs by member states of the various RECs to align them for consistency. It is also hoped that this research will impact the review of various investment instruments of the RECs with the aim of harmonising them. It is further hoped that this research would contribute to addressing the challenges that militate against the achievement of the goals of Africanising ILL for sustainable development. Originality/value: The study is original. It has not been published previously and the authors have found no existing publication that addresses the issues covered in this study.